P‐117: The Investigation of Photo Alignment Polyimide Material for Large Size IPS Display. Issue 1 (May 2016) - Ren, Wei; Hsieh, Chung-Ching; Zhao, Yong-Chao; Zhao, Ren-Tang; Song, Yan-Jun; Li, Xiang; Zhang, Yu; Yuan, Chun-Ge; Chiu, Chung-Yi; Lee, Chia-Yu
Abstract : A new photo alignment (PA) polyimide for in‐plane switching (IPS) liquid crystal display has been presented and it has good alignment performance. It realizes alignment by irradiating linearly polarized light with wavelength of 313nm. In this paper, we have study a novel 313nm PA polyimide with only one UV step. And we also have investigated the relationship between the image sticking performance and PA polyimide structure. The optical and image sticking performance of different PA polyimide are discussed in IPS mode, respectively.